(untitled) (Indian Journal of Animal Production and Management, 2015)
The effect of housing systems on reproductive disorders and performance were studied on Sixteen advanced pregnant Holstein Fresian cows and randomly divided equally into two groups of eight animals each (Group A as under conventional tie barn housing system and Group B as under loose housing system). Both the groups were reared under similar system of feeding and management except housing system. Most of the major parameters of reproductive disorder and reproductive performance showed non-significant (P < 0.05) differences between conventional and loose housing system. Total cost involved per day was significantly higher (P < 0.05) in case of conventional housing when compared with loose housing system. Cost of fodder, treatment and miscellaneous items were did not differ significantly between housing system. Average weekly milk production was significantly higher (P<0.01) in loose housing (19.54 ± 0.26 kg/day) than in conventional housing system (18.26 ± 0.25 kg/day) rearing of cows under loose housing gives better milk production without affecting reproductive performance with minimum occurrence of reproductive disorders and minimum time utilization for feeding and cleaning except during milking time, than conventional housing system. Moreover, the rearing of cattle under loose housing system was cost effective than the conventional housing system.